2012
DOI: 10.1186/1741-7015-10-102
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-22 predicts severity and death in advanced liver cirrhosis: a prospective cohort study

Abstract: BackgroundInterleukin-22 (IL-22), recently identified as a crucial parameter of pathology in experimental liver damage, may determine survival in clinical end-stage liver disease. Systematic analysis of serum IL-22 in relation to morbidity and mortality of patients with advanced liver cirrhosis has not been performed so far.MethodsThis is a prospective cohort study including 120 liver cirrhosis patients and 40 healthy donors to analyze systemic levels of IL-22 in relation to survival and hepatic complications.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 33 publications
3
34
0
Order By: Relevance
“…Concurring with other studies originating from Europe, 5,6 we recently defined a serum IL-22 concentration of 18 pg/mL as the threshold, discriminating normal from elevated systemic levels of this cytokine. 4 In agreement with our previous data, we found herein also in HCC patients that elevated IL-22 levels (>18 pg/mL, R&D Systems, Quantikine) were significantly associated with shorter overall survival (OS) (P 5 0.035, hazard ratio [HR] 0.491, 95% confidence interval [CI] 0.254-0.950) (Fig. 1).…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Concurring with other studies originating from Europe, 5,6 we recently defined a serum IL-22 concentration of 18 pg/mL as the threshold, discriminating normal from elevated systemic levels of this cytokine. 4 In agreement with our previous data, we found herein also in HCC patients that elevated IL-22 levels (>18 pg/mL, R&D Systems, Quantikine) were significantly associated with shorter overall survival (OS) (P 5 0.035, hazard ratio [HR] 0.491, 95% confidence interval [CI] 0.254-0.950) (Fig. 1).…”
supporting
confidence: 80%
“…3 We have recently found an association between disease severity as well as overall survival with IL-22 serum levels in patients with advanced liver cirrhosis. 4 In light of the emerging key role of IL-22 in hepatocellular carcinoma (HCC), 3 we assessed serum IL-22 levels in a cohort of 156 HCC patients (79.5% males) with mainly alcoholic and hepatitis C virus (HCV)-related liver disease. Concurring with other studies originating from Europe, 5,6 we recently defined a serum IL-22 concentration of 18 pg/mL as the threshold, discriminating normal from elevated systemic levels of this cytokine.…”
mentioning
confidence: 99%
“…Studies of the molecular processes underlying fibrosis in the liver have suggested that IL-22 can reduce fibrosis by inducing apoptosis of the HSCs through activation of the STAT3, p53 and SOCS3 (suppressor of cytokine signaling 3) pathways [76]. Human cases of hepatic cirrhosis have been found to express enhanced (upregulated) levels of IL-22, which has been correlated with the development of hepatorenal syndrome, ascites and reduced survival [77]. Because IL-22 has the capacity to reduce hepatic fibrosis, its upregulated level has been proposed as a predictive biomarker for assessing prognosis of hepatic cirrhosis cases in clinic [78].…”
Section: Il-22mentioning
confidence: 98%
“…However, a number of studies have previously described a raised level of IL-22 in sera as well as in hepatocytes. A positive correlation was found between the severity of liver disease and level of IL-22 in cirrhotic patients or hepatitis B virus (HBV) patients [28, 43, 51]. In some ailments, IL-22 may lead to inflammation.…”
Section: Role Of Il-22 and Il-22bp In Preventing Liver Fibrosismentioning
confidence: 99%